Boosting the mechanical and fracture resistance of asphalt via biomimetic poly dopamine‐octadecylamine aramid fiber interface. Issue 2 (30th July 2021) - Zhu, Zhaorong; Liu, Yu; Subhan, Sidra; Ma, Liangcai; Zhao, Zhenxia; Li, Jing
Abstract: Weak interfacial effect between fiber and asphalt is considered to be main limitation in the extensive improvement of composite materials. Herein, a weaker interfacial layer between fiber and asphalt has extensively been modified via non‐destructive grafting. For this, poly dopamine (PDA) with highly active sites and lipophilic octadecylamine (ODA) with strong absorption were aimed to composite with aramid fiber (AF) as AF‐PDA‐ODA following biomimetic chemistry; hence the interfacial influence on asphalt was investigated. Fourier transform infrared spectroscopy showed that AF‐PDA‐ODA composite was successfully prepared, which generated an effective chemical coupling reaction with asphalt. Contact angle measurement and specific surface analyzer tests confirmed that AF‐PDA‐ODA has better lipophilicity and larger specific surface area. Fluorescence microscopy tests confirmed that AF‐PDA‐ODA formed a uniformly developed network structure over asphalt, whereas scanning electron microscopy confirmed the "wave" structure of AF‐PDA‐ODA asphalt with stress buffering. Additionally, the adhesion was calculated via dynamic rheological shear apparatus where the tensile test showed that PDA‐ODA polymer interface layer enhanced the asphalt's fracture resistance as well as the mechanical properties of the asphalt has effectively been improved. This could provide an alternative asphalt material with enhanced adhesion and mechanical resistance properties in construction and building. Abstract :